Moderate-severe coronary calcification predicts long-term cardiovascular death in CT lung cancer screening: The ITALUNG trial. Issue 145 (December 2021) - Mascalchi, Mario; Puliti, Donella; Romei, Chiara; Picozzi, Giulia; De Liperi, Annalisa; Diciotti, Stefano; Bartolucci, Maurizio; Grazzini, Michela; Vannucchi, Letizia; Falaschi, Fabio; Pistelli, Francesco; Gorini, Giuseppe; et al.
Abstract: Purpose: Coronary artery calcifications (CAC) are very strong indicators for increased cardio-vascular (CV) risk and can be evaluated also in low-dose computed tomography (LDCT) for lung cancer screening. We assessed whether a simple and fast CAC visual score is associated with CV mortality. Methods: CAC were retrospectively assessed by two observers using a 4-score (absent, mild, moderate and severe) scale in baseline LDCT obtained in 1364 participants to the ITALUNG trial who had 55–69 years of age and a smoking history ≥20 pack–years. Correlations with CV risk factors at baseline and with CV mortality after 11 years of follow-up were investigated. Results: CAC were absent in 470 (34.5%), mild in 433 (31.7%), moderate in 357 (26.2%) and severe in 104 (7.6%) subjects. CAC severity correlated (≤0.001) with age, male sex, pack-years, history of arterial hypertension or diabetes, obesity and treated hypercholesterolemia. Twenty-one CV deaths occurred. Moderate or severe CAC were significantly associated with higher CV mortality after adjustment for all other known risk factors (ARR = 2.72; 95 %CI:1.04–7.11). Notably, also in subjects with none or one only additional CV risk factor, the presence of moderate-severe CAC allowed to identify a subgroup of subjects with higher CV death risk (RR = 3.66; CI95%:1.06–12.6). Conclusions: Moderate or severe CAC visually assessed in LDCT examinations for lung cancer screening are independently associated with CV mortality.